Open Abdomen Treatment in Acute Pancreatitis - Henn, Jonas; Lingohr, Philipp; Branchi, Vittorio; Semaan, Alexander; von Websky, Martin W.; Glowka, Tim R.; Kalff, Jörg C.; Manekeller, Steffen; Matthaei, Hanno (Frontiers in Surgery, 2021)
Background Severe acute pancreatitis (SAP) is a heterogeneous and life-threatening disease. While recent guidelines recommend a stepwise approach starting with non-surgical techniques, emergency laparotomy remains inevitable in certain situations. Open abdomen treatment (OAT) may follow, potentially resulting in additional risks for severe morbidity. Causative factors and clinical impact of OAT in SAP are poorly understood and therefore issue of the present study. Material and Methods A retrospective analysis of patients admitted to the Department of General, Visceral, Thoracic and Vascular Surgery at University of Bonn suffering from acute pancreatitis (ICD K.85) between 2005 and 2020 was performed. Medical records were screened for demographic, clinical and outcome parameters. Patients who received primary fascial closure (PFC) were compared to those patients requiring OAT. SAP-specific scores were calculated, and data statistically analyzed (P=0.05). Results Among 430 patients included, 54 patients (13%) had to undergo emergency laparotomy for SAP. Patients were dominantly male (72%) with a median age of 51 years. Indications for surgery were infected necrosis (40%), suspected bowel perforation (7%), abdominal compartment syndrome (5%), and acute intraabdominal hemorrhage (3%). While 22 patients (40%) had PFC within initial surgery, 33 patients (60%) required OAT including a median of 12 subsequent operations (SD: 6, range: 1-24). Compared to patients with PFC, patients in the OAT group had significantly fewer biliary SAP (P=0.031), higher preoperative leucocyte counts (P=0.017), higher rates of colon resections (P=0.048), prolonged ICU stays (P=0.0001), and higher morbidity according to Clavien-Dindo Classification (P=0.002). Additionally, BISAP score correlated positively with the number of days spent at ICU and morbidity (P=0.001 and P=0.000002). Both groups had equal mortality rates. Discussion Our data suggest that preoperative factors in surgically treated SAP may indicate the need for OAT. The procedure itself appears safe with equal hospitalization days and mortality rates compared to patients with PFC. However, OAT may significantly increase morbidity through longer ICU stays and more bowel resections. Thus, minimally invasive options should be promoted for an uncomplicated and rapid recovery in this severe disease. Emergency laparotomy will remain ultima ratio in SAP while patient selection seems to be crucial for improved clinical outcomes.